Pengaruh Leadership, Communication dan Kompetensi Terhadap Kinerja Karyawan Point Coffee Medan - Etri Rode Wisna Wati; Muhammad Toyib Daulay; Insan, Muhammad Yaizamul (Jurnal Riset Rumpun Ilmu Ekonomi, 2025)
This study aims to assess extent to which leadership, communication, and competence influence employee performance at Point Coffee Medan. The research was motivated by field findings that indicated a decline in work quality, such as delays in task completion, miscommunication among employees, and a lack of capability in carrying out tasks effectively. These issues highlight the need for improvements in human resource aspects, particularly in leadership style, communication effectiveness, and employee competence. A quantitative research method with a descriptive approach was employed. Data were collected through questionnaires distributed to 38 employees of Point Coffee Medan. The research instruments were tested for validity and reliability, and the data were analyzed using multiple linear regression. The goal of the study was to determine both the partial and simultaneous effects of the three independent variables on employee performance. The analysis results indicate that leadership, communication, and competence have a positive and significant impact on performance, both individually and collectively. Effective leadership helps guide and motivate employees in completing their tasks. Clear and open communication fosters collaboration and a harmonious work environment. Meanwhile, strong competence enables employees to work more efficiently, accurately, and productively. In conclusion, the improvement of employee performance is strongly influenced by the leader's ability to manage the team, the quality of internal communication, and the mastery of work-related competencies. Therefore, the company is advised to enhance these three aspects as part of its human resource management strategy